An Interactive Tool for Simulation of Biological Models Into the Wastewater Treatment With Microalgae - Sánchez-Zurano, A.; Guzmán, J. L.; Acién, F. G.; Fernández-Sevilla, J. M. (Frontiers in Environmental Science, 2021)
This paper presents a novel simulation tool to understand and to analyze biological models for wastewater treatment processes using microalgae. The models for this type of processes are very complex to be analyzed because of very different phenomena, variables and parameters involved. The model already included into the tool has been validated at controlled conditions simulating outdoor ones, it being useful to simulate real outdoor cultures. The major contribution of the proposed tool is that these models can be easily and interactively simulated and compared. The tool allows to simulate biological models only considering microalgae or including the microalgae-bacteria consortium. Moreover, the simulations can be done only using the solar radiation contribution or by adding the environmental and bacteria effects as cardinal terms. Furthermore, effects of the wastewater properties or different microalgae strain can be evaluated. The interactive simulations can be performed for selected days as representative of the different year seasons that are already preloaded in the tool. However, the user can also load data from other locations to simulate the models under particular conditions.